Gaining insight into patients' experience of adherence to hypertensive treatment - Lee, Khuan; Mohd Yunus,; Loong, Yik Yee; Ahmad, Shamsuddin; Jamil, Zubaidah; Abdul Raman, Rosna (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2010)
Hypertension is one of the major risk factors for coronary heart disease and the most important factor for cerebrovascular diseases. Adherence to treatment is a fundamental pre-requisite for therapeutic benefit in hypertensive patients. Adherence is a complex behavioural process that is strongly influenced by the way in which patients live, as well as the psychological and social support system. Aim: To understand and conceptualize the experience of people on long-term antihypertensive treatment Method: Qualitative analysis using semi-structured interviews with ten hypertensive patients from the medical clinic of Kuala Lumpur General Hospital. Results: Although the participants were aware of having high blood pressure they declined receiving any treatment at the early stage of the disease. Fear of death and disease complications are reinforcements for participants to adhere to medication. They perceived the label of "hypertension" will affect their self-identity and social role. Positive thinking regarding medication assists participants to adhere to treatment. Conversely, participants who perceived medication negatively also adhere to a medication regime, as adherence behaviour satisfies the family. Participants justified modifying their regimen or taking Complementary and Alternative Medicine (CAM) as they believe know the their body best. However, participants wished to obtain more information regarding hypertension and its treatment from the doctors. Conclusion: In finding the fine balance between stepping in and holding back treatment and care, health professionals need to know their clients in context. This balance can only be achieved by establishing processes of negotiation within an ongoing therapeutic relationship.